Study on the New Path of Chinese Commercial Banks' Globalization Development - Guo, Xingwen (International Journal of Global Economics and Management, 2024)
The globalization process of Chinese commercial banks stands at a significant historical juncture. With the increasing integration of global financial markets, China's economic power is progressively infiltrating the international arena. As vital agents of economic development, commercial banks must adapt to this trend and accelerate their internationalization efforts. However, amid the wave of globalization, Chinese commercial banks face unprecedented challenges and opportunities. On one hand, the intensifying competition in global markets and the growing complexity and uncertainty of the international financial system necessitate higher-level strategic planning. On the other hand, the rapid advancement of technology and the rise of the digital economy offer new avenues for development. Identifying an appropriate strategic position globally and achieving sustainable business growth has become a pressing issue for Chinese commercial banks. This study focuses on exploring how Chinese commercial banks can navigate the globalization process through innovative strategies, regional differentiation approaches, and multinational collaboration to find new paths that adapt to the global market, thereby securing a competitive edge in the international arena.